Development and Training Application for Receiving and Responding to Community Complaints “SMART REPORT” at Department of Education and Culture of East Kalimantan - Ita Arfyanti; Bartolomius Harpad; Yunita Yunita; Sony Darmawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This public service aims to build a Community Complaints Receipt and Response Application “Smart Report” in the Office of Department of Education and Culture of East Kalimantan. This application was developed using Sublime Text 3, XAMPP software which is a combination of Apache Web Server, PHP, and MySQL. The method of data collection uses the observation method and system development methods using the waterfall. Because this method has stages that are clearly real and practical. Then testing the system is Black Box and Beta Testing, so that the system is obtained in accordance with the wishes of prospective users. Application for receiving and responding to community complaints “Smart Report”. The purpose of this public service is to be able to simplify or produce a response that is relatively fast, precise and can be done without time constraints. It is expected that this information system can overcome the problems that have occurred so far in the process of complaints and community responses